Inclusión de micropilotes como elementos recuperadores de carga en cimentaciones: revisión del estado del conocimiento - Castellanos Guerrero, Wendy Madeleyne; Rodriguez Rincón , Edgar (Ingeniería, 2022)
Context: Micropiles are used as reinforcing or underpinning elements, a function that has been tested and analyzed by different authors. In Colombia, the use of this technique is limited to the geotechnics expert’s own concepts, which consists of empirical knowledge and successful experiences. Consequently, it is necessary to compile key variables and analytical and numerical methodologies for a better understanding of this technique. Method: This document presents a state of the art supported by articles and research aimed at analyzing and evaluating the behavior of micropiles as load capacity recovery elements in groups of piles with defects. Results: The findings identified in the consulted documents are synthesized as a theoretical support that will become a starting point for future research in this field of geotechnical engineering. Conclusions: It is possible to evidence that micropiles have a positive influence on the load recovery of existing foundations, thus demonstrating the importance of conducting field tests and analyses directly in Colombia, considering the specific strata of soils found in the country.